OPTIMASI KEUNTUNGAN USAHA HOMEMADE KUE BASAH MENGGUNAKAN PEMROGRAMAN LINEAR METODE SIMPLEKS - M. Fadli Pratama; Arya Permana Sadewa, Paduloh (ADISAM PUBLISHER, 2025)
This study aims to optimize the profit of homemade wet cake businesses using linear programming with the Simplex method. Small and medium-sized enterprises (SMEs) in Indonesia are rapidly growing, and in the food industry sector, SMEs face challenges in managing limited resources to maximize profits. A mathematical model using linear programming is designed to assist SMEs in determining efficient resource allocation strategies. This research identifies decision variables, raw material constraints, and production capacity to maximize profits using the Simplex method. The method is applied to wet cake businesses, considering the constraints related to raw materials and production capacity. The data obtained includes information about raw materials, selling prices, production costs, and available production capacity. The mathematical model is structured with an objective function to maximize profits and constraints related to raw material limitations and production capacity. The calculations using the Simplex method show the optimal solution for resource allocation, which can improve production efficiency and profit. Thus, linear programming with the Simplex method provides significant contributions to SMEs in managing resources efficiently and adaptively, potentially enhancing competitiveness in the competitive market. This research also opens up opportunities for the application of similar methods in other SME businesses within the food industry sector